Javanese Mystique, Modernity, and Islamism: Radical Subjects in the Works of Iman Budhi Santosa - Angga Trio Sanjaya (SUAR BETANG, 2023)
The purpose of this study is to examine the resistance of Javanese mysticism in the face of modernity and Islamism in the life of Iman Budhi Santosa as well as to analyze the emergence of radical subjects in the context of his poetry. This research uses a descriptive approach with Fairclough's Critical Discourse Analysis (AWK). Data collection techniques in this study apply the observing method, advanced note-taking techniques, and document review techniques. The results of the research show that (1) a study of the text dimension shows that there is a referential action towards the Javanese mystical tradition through metaphors in the poems of Iman Budhi Santosa; (2) The study of the dimensions of discursive practice shows that the aspect of text production in Iman Budhi Santosa's work departs from Javanese literature, especially Javanese mysticism; (3) The study of the dimensions of social praxis shows that there is a form of Javanese mystical resistance to modernist and Islamist discourses as well as radical actions carried out through 'moments of emptiness'. Based on the results, this research is important as part of linguistic research which eclecticly accommodates various perspectives and discourses, especially Critical Discourse Analysis (AWK), poststructuralist, radical psychoanalysis, and modernity discourse.AbstrakTujuan dari penelitian ini adalah menelaah resistensi mistik Jawa dihadapan modernitas dan Islamisme dalam kehidupan Iman Budhi Santosa sekaligus menganalisis munculnya subjek radikal dalam konteks kepenyairannya. Metode penelitian ini menggunakan diskriptif dengan pendekatan Analisis Wacana Kritis (AWK) Fairclough. Teknik Pengumpulan data dalam penelitian ini menerapkan metode simak dan teknik lanjutan catat, dan teknik telaah dokumen. Hasil penelitian menunjukkan bahwa (1) Telaah terhadap dimensi teks menunjukkan adanya tindakan referensial terhadap tradisi mistik Jawa melalui metafora dalam puisi-puisi Iman Budhi Santosa; (2) Telaah terhadap dimensi praktik diskursif menunjukkan aspek produksi teks dalam karya Iman Budhi Santosa berangkat dari kepustakaan Jawa khsusnya mistik Jawa; (3) Telaah dimensi praksis sosial menunjukkan adanya bentuk resistensi mistik Jawa terhadap wacana modernistas dan islamisme serta tindakan radikal yang dilakukan melalui ‘momen kekosongan’. Berdasarkan hasil pembahasan, penelitian ini penting keberadaanya sebagai bagian dari penelitian linguistik yang secara eklektis mengakomodir berbagai perspektif dan wacana khususnya Analisis Wacana Kritis (AWK), postrukturalis, psikoanalisis radikal, maupun wacana modernitas.